Membrane filtration of manganese (II) remediated-microalgae: manganese (II) removal, extracellular organic matter, and membrane fouling - Sim, Lee Nuang (2022)
This study investigated the biosorption efficiency of Mn (II) by algae (Thalassiosira pseudonana) and membrane performance in a hybrid algae-membrane system. The presence of Mn (II) at 2–10 mM could influence (i.e., at lower algal inoculation ratio of OD = 0.1) or showed negligible effect (i.e., at higher inoculation ratio of OD = 0.17), on algal growth, cell morphology, pigment content, and extracellular organic matter production. The Mn (II) removal was mainly attributed to the algal uptake mechanisms; and higher removal efficiency (>66%) was achieved at higher algal inoculation ratio. Although increasing the Mn (II) concentration could reduce the algal uptake ratio of Mn (II), the membrane performance was improved. The optical coherence tomography (OCT) analysis revealed that the specific volume of cake layer increased gradually over time, however, the irreversible fouling was predominant and associated the presence of building blocks in soluble organics.